2019
DOI: 10.3892/mmr.2019.10630
|View full text |Cite
|
Sign up to set email alerts
|

miR‑519d‑3p promotes TGFβ/Smad mediated postoperative epidural scar formation via suppression of BAMBI

Abstract: To investigate the role of microrna (mir)-519d-3p in postoperative epidural scar formation and its regulation of the bone morphogenetic protein and activin membrane-bound inhibitor (BaMBi), mir-519d-3p and BaMBi expression levels in the lumbar disc of patients who had undergone laminectomy were detected with reverse transcription-quantitative polymerase chain reaction and western blotting. The results demonstrated that miR-519d-3p expression was significantly increased, whereas BaMBi expression was sharply red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…For example, BAMBI has been shown to inhibit skin fibrosis in keloids by suppressing TGF-β1-induced hyper normal fibroblast proliferation and excessive type I collagen accumulation [ 39 ]. Consistent with this finding, suppression of BAMBI by miR-519d-3p promoted TGFβ/Smad-mediated postoperative epidural scar formation [ 40 ]. Modulation of BAMBI, however, not only affected ECM formation.…”
Section: Discussionsupporting
confidence: 57%
“…For example, BAMBI has been shown to inhibit skin fibrosis in keloids by suppressing TGF-β1-induced hyper normal fibroblast proliferation and excessive type I collagen accumulation [ 39 ]. Consistent with this finding, suppression of BAMBI by miR-519d-3p promoted TGFβ/Smad-mediated postoperative epidural scar formation [ 40 ]. Modulation of BAMBI, however, not only affected ECM formation.…”
Section: Discussionsupporting
confidence: 57%
“…A growing body of evidence suggests that microRNA signaling plays a vital role in fibroblast cellular behavior and the development of fibrotic activity originating from surgical scar tissue [37]. In addition, miR-519d-3p [38] and miR-146 [39] may serve as diagnostic biomarkers for the early detection of epidural fibrosis and further upregulation of enhanced fibroblast proliferation and inflammatory response in epidural fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…In previous mechanism studies it was reported that transforming growth factor (TGF)β signaling is a key factor in the regulation of fibrosis (Meng et al, 2016). miR-27 and miR-519d were confirmed to mediate fibroblast activation and epidural fibrosis by targeting the TGFβ signaling pathway (Zeng et al, 2017;Yang L et al, 2019). Besides, the accumulation of collagen was also a principal cause of epidural fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, miRNAs could negatively regulate the expression of target genes by binding to the 3'UTR of target mRNA molecules, thus miRNAs have been reported to be involved in various biological processes, such as carcinogenesis (Chen et al, 2019;Nariman-Saleh-Fam et al, 2019), anticancer effect (Tao et al, 2018;Yang J et al, 2020), neuro-protection (Song et al, 2019;Xiao et al 2019), as well as epidural fibrosis (Lin et al, 2018). For example, an investigation on the role of miR-519d-3p in postoperative epidural scar formation and found that the overexpression of miR-519d-3p promoted the proliferation of fibroblasts and the expression of type I collagen, which are important factors in epidural fibrosis (Yang L et al, 2019). Previously, it has been demonstrated that the prolapse of the intervertebral nucleus pulposus would lead to an epidural inflammation (McCarron et al, 1987).…”
Section: Introductionmentioning
confidence: 99%